Preferential Trading in South Asia - Baysan, Tercan; Panagariya, Arvind; Pitigala, Nihal (World Bank, Washington, DC, 2012)
The authors examine the economic case for the South Asia Free Trade Area (SAFTA) Agreement signed on January 6, 2004 by India, Pakistan, Bangladesh, Sri Lanka, Nepal, Bhutan, and the Maldives. They start with a detailed analysis of the preferential trading arrangements in South Asia to look at the region's experience to date and to draw lessons. Specifically, they examine the most effective free trade area in existence-the India-Sri Lanka Free Trade Area-and evaluate the developments under the South Asian Preferential Trade Area (SAPTA). The authors conclude that, considered in isolation, the economic case for SAFTA is weak. When compared with the rest of the world, the region is tiny both in terms of economic size as measured by GDP (and per capita incomes) and the share in world trade. It is argued that these facts make it unlikely that trade diversion would be dominant as a result of SAFTA. This point is reinforced by the presence of high levels of protection in the region and the tendency of the member countries to establish highly restrictive "sectoral exceptions and sensitive lists" and stringent "rules of origin." The authors argue that the SAFTA makes sense only in the context of a much broader strategy of creating a larger preferential trade area in the region that specifically would encompass China and the member nations of the Association of South East Asian Nations. In turn, the case for the latter is strategic: the pursuit of regionalism in the Americas and Europe has created increasing discrimination against Asian exports to those regions, which must inevitably affect the region's terms of trade adversely. An Asian bloc could be a potential instrument of changing incentives for the trade blocs in the Americas and Europe and forcing multilateral freeing of trade. Assuming that the SAFTA Agreement is here to stay, the authors suggest steps to ensure that the Agreement can be made more effective in promoting intra-regional trade, while minimizing the likely trade-diversion costs and maximizing the potential benefits.